Perception of adolescent girls about their well-being - Mahbub, Amina (BRAC Research and Evaluation Division (RED), 2020)
This qualitative study was initiated to explore adolescent girls' perceptions about wellbeing. A part of the BRAC-ICDDR,B joint research project on health and well-being, the study was done purposively in two villages of Matlab Thana among the adolescent girls of BRAC School aged from 11 to 14 years. Mainly Focus Group Discussions (FGD) were done for data collection, but during FGDs, freelisting and importance rating exercises were conducted as well. In the study the adolescent girls presented a set of indicators of well-being condition from their perspective. They highly prioritized some indicators for better living like father s/brothers income, good relations with the family members, healthy body without any illness and education. In developing linkages between the identified indicators, they started with two points i.e. father' s/brother's income and income from own poultry and shared livestock. The girls pointed out some socioeconomic and cultural barriers to achieve a well-being condition. However, the study suggested that the findings could be useful to design or measure the effect of interventions on adolescent's well-being.